Effect of Soft Interlayer Dip Angle on the Attenuation and Prediction of Blast-Induced Vibrations in Rock Slopes: An Experimental Study - Sheng Chen; Nan Jiang; Ying Sun; Jian Pan; Liping He; Jianxiong Guo; Jikui Zhang; Zicheng Zhang (Applied Sciences, 2025)
Rock slopes containing weak interlayers are highly prone to instability under the disturbance of blasting vibrations due to the influence of structural planes. To address the limitations of traditional models in predicting vibration attenuation for such slopes, this study conducted in situ blasting tests on sand–mudstone interbedded slopes from the Pinglu Canal project. Based on dimensional analysis, the Sadowsky formula was modified to incorporate both elevation difference (H/R) and soft interlayer dip angle (θ), resulting in an enhanced predictive model. Field data revealed that the proposed model significantly improved prediction accuracy, with determination coefficients (r2) increasing from 0.847 to 0.9946 in the vertical (Z) direction. Compared to traditional models, the root mean square error (RMSE) decreased by 96%, demonstrating superior capability in capturing vibration attenuation influenced by geological heterogeneity. Key findings reveal that steeper interlayer dip angles significantly accelerate PPV attenuation, particularly in the X direction. These findings provide a critical tool for optimizing blasting parameters in layered rock slopes, effectively mitigating collapse risks and enhancing construction safety. The model’s practicality was validated through its application in the Pinglu Canal project, offering a paradigm for similar engineering challenges in complex geological settings.